Pengaruh Dukungan Keluarga dan Pekerjaan Ibu terhadap Pemberian MP-ASI sebelum Bayi Berusia 6 Bulan di Puskesmas Asologaima - Farlikhatun, Lili; Tapatkeding, Yulianti (Universitas Malahayati, 2025)
ABSTRACT A preliminary study at the Asologaima Health Center in November 2024 showed that there were 320 babies aged 0-6 months, of whom 225 (70%) received exclusive breastfeeding, while 94 (30%) babies aged 0-6 months had been given complementary foods. The results of a preliminary study on November 23, 2024, obtained from 10 mothers with children aged 0-6 months, 6 respondents (60%) had been given complementary foods to their babies before the age of 6 months. Providing food to babies is the mother's responsibility, and providing complementary foods to babies under 6 months of age indicates a failure in providing exclusive breastfeeding. Providing complementary foods before the age of 6 months can affect the baby's health, such as diarrhea, because the baby's digestive system is not ready to receive food other than breast milk. The aim is to determine the effect of family support and maternal employment on the provision of complementary feeding before the baby is 6 months old at the Asologaima Health Center in 2024. Using a correlational analytical design with a cross-sectional approach. The study sample consisted of 35 mothers who had babies aged less than 6 months with a purposive sampling technique. The statistical test used was the Chi-Square test. The Chi-Square test showed that family support did not have a significant effect on the provision of complementary feeding (p = 0.324), while maternal employment had a significant effect on the provision of complementary feeding (p <0.001). There was no significant effect between family support and the provision of complementary feeding. However, maternal employment has a significant effect on the provision of complementary feeding before the baby is 6 months old at the Asologaima Health Center. It is hoped that the Asologaima Health Center can improve education regarding the importance of exclusive breastfeeding, pay attention to maternal employment factors in supporting breastfeeding, and provide facilities that support working mothers. Keywords: Family Support, Employment, Provision of Complementary Feeding Before The Baby Is 6 Months Old ABSTRAK Studi pendahuluan di Puskesmas Asologaima pada bulan November 2024 jumlah bayi 0-6 bulan sebanyak 320 bayi, yang mendapatkan asi eklusif sebanyak 225 (70%), sedangkan sebanyak 94 (30%) bayi usia 0-6 bulan sudah diberikan makanan pendamping ASI. Hasil studi pendahuluan pada tanggal 23 November 2024 di dapatkan dari 10 ibu yang memiliki anak usia 0-6 bulan sebanyak 6 responden (60%) sudah diberikan MPASI pada bayi sebelum usia 6 bulan.Pemberian makanan pada bayi adalah tanggung jawab ibu, dan pemberian Makanan Pendamping ASI (MP-ASI) pada bayi di bawah usia 6 bulan menunjukkan kegagalan dalam pemberian ASI eksklusif. Pemberian MP-ASI sebelum usia 6 bulan dapat memengaruhi kesehatan bayi, seperti diare, karena sistem pencernaan bayi belum siap menerima makanan selain ASI. Bertujuan untuk mengetahui pengaruh dukungan keluarga dan pekerjaan ibu terhadap pemberian MP-ASI sebelum bayi berusia 6 bulan di Puskesmas Asologaima pada tahun 2024. Menggunakan desain analitik korelasional dengan pendekatan cross-sectional. Sampel penelitian terdiri dari 35 ibu yang memiliki bayi usia kurang dari 6 bulan dengan teknik purposive sampling. Uji statistik yang digunakan adalah uji Chi-Square. Uji Chi-Squaremenunjukkan bahwa dukungan keluarga tidak berpengaruh signifikan terhadap pemberian MP-ASI (p = 0,324), sementara pekerjaan ibu berpengaruh signifikan terhadap pemberian MP-ASI (p < 0,001). Tidak ditemukan pengaruh signifikan antara dukungan keluarga dan pemberian MP-ASI. Namun, pekerjaan ibu memiliki pengaruh signifikan terhadap pemberian MP-ASI sebelum bayi berusia 6 bulan di Puskesmas Asologaima. Diharapkan Puskesmas Asologaima dapat meningkatkan edukasi mengenai pentingnya ASI eksklusif, memperhatikan faktor pekerjaan ibu dalam mendukung pemberian ASI, serta menyediakan fasilitas yang mendukung ibu yang bekerja. Kata Kunci: Dukungan Keluarga, Pekerjaan, Pemberian MP-ASI Sebelum Bayi Berusia 6 Bulan